1992
DOI: 10.1149/1.2069248
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Determination of Gibbs Energies of Formation of Calcium Chromite and Chromate

Abstract: The standard Gibbs free energies of formation of calcium chromite and calcium chromate have been determined employing solid state galvanic cells Pt, Cr + CaO + CaCr204 [[ThO2(Y20~)[[Cr + Cr203, Pt in the temperature interval 1050 < T ~< 1475 K and Pt, 02, CaO + CaF2[[CaF2[ICaF2 + Cr203 + CaCrO4, 02, Pt for 870 ~< T ~< 1100 K. Calcium chromate (CaCrO4) was found to be unstable in contact with Cr203 and O2 (1.01 x l0 s Pa) at T > 1125 K. The reversibility of the EMF was confirmed by microcoulometric titration. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…When composite CZ-51-LaCaCr samples were heated at 1200 • C for 2 h, the recorded XRD diffraction patterns displays reflects corresponding to the LaCrO 3 or CaZrO 3 phase as well as Fig. 15 presents the linear dependence of measured EMF of cell (4) in the range 800-1200 • C. The EMF values were stable for more than 2 h. The EMF results obtained from cell (5) with the electrode MCr 2 O 4 , M = Ca, Mg are in good agreement with data existing in literatures [25,31]. The overall cell reaction in the cell (5) with the MgCr 2 O 4 electrode can be described by Eq.…”
Section: Resultssupporting
confidence: 87%
“…When composite CZ-51-LaCaCr samples were heated at 1200 • C for 2 h, the recorded XRD diffraction patterns displays reflects corresponding to the LaCrO 3 or CaZrO 3 phase as well as Fig. 15 presents the linear dependence of measured EMF of cell (4) in the range 800-1200 • C. The EMF values were stable for more than 2 h. The EMF results obtained from cell (5) with the electrode MCr 2 O 4 , M = Ca, Mg are in good agreement with data existing in literatures [25,31]. The overall cell reaction in the cell (5) with the MgCr 2 O 4 electrode can be described by Eq.…”
Section: Resultssupporting
confidence: 87%
“…A similar response was noticed when Cr employing ThO 2 (Y 2 O 3 ) solid electrolyte. [17] According to the DTA results obtained in this study, shown in Figure 5, NiTiO 3 (ilm) probably undergoes an order-disorder type of transformation. The critical transformation temperature obtained in this study (T c ϭ 1568 ‫ע‬ 2 K) is in good agreement with that reported by Lerch and Laqua [13] (T c ϭ 1563 K) from the DTA measurements.…”
Section: Discussionmentioning
confidence: 52%
“…The standard Gibbs free energy of the formation of CaCrO 4 was determined in a few studies. [17][18][19][20] In the following formation reaction of Figure 3 shows the free-energy diagram for the formation of CaCrO 4 , CaO, and Cr 2 O 3 based on these results, in which the annealing conditions of high and low partial pressures of oxygen employed in the present study are also plotted.…”
Section: Xrd Analysesmentioning
confidence: 99%